School and learning from the perspective of elementary school students - Rajović Ranko D.; Budić Spomenka M.; Radulović Branka N. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2020)
The paper deals with examining the opinions of the seventh and eighth-grade students on school, learning and of their rapport towards doing homework. The research included 286 students of seventh and eighth grade in four elementary schools in Serbia. The data were collected via survey method and processed using the SPSS software package. The questionnaire was the instrument used in the research, and descriptive-analytical method was used for data interpretation. The research results demonstrate that students with excellent academic performance show a high level of responsibility concerning regular studying, whilst students with good and satisfactory academic performance do not. Likewise, the students with excellent academic performance to a greater extent perceive studying as a positive activity, in comparison to the students with poorer academic performance. A positive correlation of medium intensity was recorded between the variables of regular studying and doing homework regularly. However, the percentage of students who stated they did not do their homework regularly due to the lack of motivation, homework overload or insufficiently clear expectations is not negligible. They describe school as a well-equipped, safe and stimulating environment with strict teachers. This research contributes to the understanding of the role of school from the perspective of the students atswhom the goals of school studying are directed.